2006
DOI: 10.1002/chin.200615111
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Antimicrobial Activity of Some 3‐Alkyl‐4‐(arylmethyleneamino)‐4,5‐dihydro‐1H‐1,2,4‐triazol‐5‐ones.

Abstract: Pyrazole derivatives R 0180Synthesis and Antimicrobial Activity of Some 3-Alkyl-4-(arylmethyleneamino)-4,5-dihydro-1H-1,2,4-triazol-5-ones. -The new acetate (III) and hydrazine derivatives (IV) of the title triazolone system are synthesized. They show significant antibacterial, antifungal and antipseudomonal activities. -(KAHVECI*, B.; BEKIRCAN, O.; KARAOGLU, S. A.; Indian J. Chem., Sect. B: Org. Chem. Incl. Med. Chem. 44 (2005) 12, 2614-2617; Dep. Chem., Karadeniz Tech. Univ., TR-53100 Rize, Turk.; Eng.) -A. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 0 publications
0
17
0
Order By: Relevance
“…For example, fluconazole is used as an antimicrobial drug [17], while vorozole, letrozole and anastrozole are non-steroidal drugs used for the threatment of cancer [18] and loreclezole is used as an anticonvulsant [19]. Furthermore, in recent years some Schiff base derivatives of 1,2,4-triazoles and their reduced derivatives have been also found to possess pharmacological activities [20][21][22][23][24][25][26]. These biological data prompted us to synthesize some new bis-1,2,4-triazole derivatives, and in the present study, a novel series of bis-Schiff base derivatives resulting from the reaction of 4-amino-3-aryl-5-phenyl-4H-1,2,4-triazoles 3 with bis-aldehydes 1 and their corresponding reduced derivatives were synthesized and characterized by IR, 1 H-NMR, 13 C-NMR and mass spectral data.…”
Section: Introductionmentioning
confidence: 99%
“…For example, fluconazole is used as an antimicrobial drug [17], while vorozole, letrozole and anastrozole are non-steroidal drugs used for the threatment of cancer [18] and loreclezole is used as an anticonvulsant [19]. Furthermore, in recent years some Schiff base derivatives of 1,2,4-triazoles and their reduced derivatives have been also found to possess pharmacological activities [20][21][22][23][24][25][26]. These biological data prompted us to synthesize some new bis-1,2,4-triazole derivatives, and in the present study, a novel series of bis-Schiff base derivatives resulting from the reaction of 4-amino-3-aryl-5-phenyl-4H-1,2,4-triazoles 3 with bis-aldehydes 1 and their corresponding reduced derivatives were synthesized and characterized by IR, 1 H-NMR, 13 C-NMR and mass spectral data.…”
Section: Introductionmentioning
confidence: 99%
“…FTIR spectrum showed disappearance of absorption band for NH 2 group and appearance of the absorption band at (1668-1647)cm -1 to (C=N) [19] and show other different absorption bands for the substituted groups that are listed in Table (1). 1 HNMR spectrum for ( ) w υ 7.30-8.42 ppm; υ8.65 ppm (s, 1H, -N=CH-); υ 9.16 ppm (s, 1H, -CS-NH-Ph); (m, 13H, Ar-H) and υ10.30 ppm (s, 1H, -CO-NH-CS-) [20 figure (1). 13 CNMR spectrum for this compound show signals listed in Table (7) and figure (2). Schiff bases were cyclized by using four different steps with different reagents.…”
Section: Compmentioning
confidence: 98%
“…These compounds can be formed by react the primary amines with aldehydes or ketones in presence either acid, base or heat as a catalyst of the reaction [1]. Great deals of research have reported that Schiff bases which are derived from the heterocyclic compounds are antimicrobial [2], antiproliferative [3], anticonvulsant [4], cytotoxic [5] and anticancer [6]. Like the other organic compounds, schiff bases which consist of four, five and seven membered rings have biological activities based on its spectrum therefore many of industrial and medical applications like pigments and dyes take place in these fields [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, Schiff bases derived from various heterocycles have been reported to possess cytotoxic [2], anticonvulsant [3], antiproliferative [4], antimicrobial [5], anticancer [6], and antifungal activities [7]. Mannich bases have gained importance due to their application in pharmaceutical chemistry.…”
Section: Introductionmentioning
confidence: 99%